2022
DOI: 10.3389/fonc.2022.955807
|View full text |Cite
|
Sign up to set email alerts
|

Full-course resection control strategy in glioma surgery using both intraoperative ultrasound and intraoperative MRI

Abstract: BackgroundIntraoperative ultrasound(iUS) and intraoperative MRI (iMRI) are effective ways to perform resection control during glioma surgery. However, most published studies employed only one modality. Few studies have used both during surgery. How to combine these two techniques reasonably, and what advantages they could have for glioma surgery are still open questions.MethodsWe retrospectively reviewed a series of consecutive patients who underwent initial surgical treatment of supratentorial gliomas in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…53 The combination of ioUS for real-time intraoperative resection monitoring coupled with subsequent iMRI for the assessment of resection completion (the so-called full-course resection strategy) was investigated in a recent retrospective study of 40 patients. 54 This combination of ioUS and iMRI yielded a final EOR rate of 95.43% and GTR rate of 72.5%, with reduced surgical time and fewer total MRIs compared with other studies of iMRI. Although preliminary, these results demonstrate the ease of combining ioUS with other methods or assessing EOR.…”
Section: Intraoperative Ultrasoundmentioning
confidence: 78%
“…53 The combination of ioUS for real-time intraoperative resection monitoring coupled with subsequent iMRI for the assessment of resection completion (the so-called full-course resection strategy) was investigated in a recent retrospective study of 40 patients. 54 This combination of ioUS and iMRI yielded a final EOR rate of 95.43% and GTR rate of 72.5%, with reduced surgical time and fewer total MRIs compared with other studies of iMRI. Although preliminary, these results demonstrate the ease of combining ioUS with other methods or assessing EOR.…”
Section: Intraoperative Ultrasoundmentioning
confidence: 78%
“…Nevertheless, the performance of iUS in localization of residual tumor is considered promising. Multiple studies have reported that navigated iUS shows to be a good addition to the neurosurgical armamentarium [9,13,14,[17][18][19][20][21]. There is not yet a clear consensus in literature on the sensitivity and specificity of iUS in detecting residual tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies [9,10,13,14,[17][18][19][20][21][22], we defined that iUS has a good diagnostic value in detecting residual tumor if a sensitivity and specificity of more than 80% was achieved.…”
Section: Creating Segmentations and Quantitative Analysismentioning
confidence: 99%
“…The main technical limitations found in some study series include artifacts after opening the dura mater, variability in the frequency and amplitude of mechanical pulsation, and uncertainty in evaluating deep lesions ( 38 ). According to the latest study by Hou et al ( 41 ), combining the SWE mode with superb microvascular imaging (SMI), it was found that in the SWE mode, HGG and LGG showed completely different values under Young's modulus, with a diagnostic threshold for distinguishing HGG and LGG at 13.05 kPa. In the SMI mode, the tissue surrounding the HGG was described as having distorted blood flow signals, while the HGG tissue itself exhibited dilated and bent vessels.…”
Section: Ious Characteristics According To High-grade Glioma Subtypementioning
confidence: 99%
“…This suggests a combined approach using imaging tools. A recent retrospective study by Hou et al ( 41 ) included 40 patients who underwent IOUS and IMRI during glioma resection. IOUS was used for preoperative and intraoperative evaluations, while IMRI was used for final scanning to determine whether additional resection was necessary.…”
Section: Surgical Outcomes Of High-grade Glioma Patients According To...mentioning
confidence: 99%